Nickel reduces blossom-end rot even under calcium deficiency conditions evidence from physiological responses of the NI - CA interaction - Macedo, Fernando Giovannetti; de Melo, Wanderley José [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP]; Santos, Elcio Ferreira; Cruz, Renata Beatriz; Belloti, Mariana (Taylor & Francis, 2023)
The isolated study of calcium (Ca) as a cause of blossom-end rot (BER), has not demonstrated advances in the knowledge of this physiological disorder. Recent studies have shown that the Ni-Ca interaction can increase tomato yield and reduce the incidence of BER. Thus, this work aimed to evaluate the effect of nickel (Ni) and Ca interaction on the physiology of tomato plants focusing on nutrient balance, gas exchange and activity of urease and glyoxalase I and II enzymes. Tomato plants were grown in pots with substrate. A random design was used in a 2 x 4 factorial scheme. Two Ca doses (sufficient Ca - Ca S = 0.35; and deficient Ca - Ca D = 0.70 g kg−1) and four Ni doses (0.0, 0.5, 1.0 and 2.0 mg dm−3) was used. The activity of the glyoxalases I and II were used as an indicator of a stress condition. In plants grown under Ca S, the Ni application showed an increase in leaf content of nitrogen, phosphorus, Ca, iron, zinc, boron, copper and Ni, as well the gas exchange enhanced. The urease activity increased as a function of the Ni doses increase. Plants grown with Ca S and Ni doses of 0.5 and 1.0 mg dm−3 showed the lowest glyoxalase activities. The use of Ni at the mentioned doses should be considered in tomato fertilization programs focused on BER reduction.
Keywords: blossom-end rot; glyoxalases; micronutrient